Kemampuan Adsorben dari Limbah Serbuk Gergaji Kayu Jati terhadap Penurunan Kandungan Timbal (Pb) pada Limbah Cair dengan menggunakan Sistem Batch - Firmanto, Rafli Puji; Rr. Diah Nugrahaeni Setyowati; Dedy Suprayogi (Journal of Research and Technology, 2021)
Teakwood sawdust is a by product of the sawmilling process used by industry and wood enterprises. One way to put the garbage to good use is to use it as a raw material for creating adsorbents for adsorbing heavy metals in waste water. The goal of this study is to use a batch system to investigate the ability of teakwood sawdust to adsorb lead (Pb) in liquid waste and to establish the optimal adsorption isotherm modeling in the adsorption process for the processing of lead (Pb) heavy metal waste. This is an experimental study that uses a variety of adsorbent masses, including 1 gram, 2 gram, 3 gram, 4 gram, and 5 gram, as well as a variety of adsorbent activation methods.According to the study's findings, variations in the mass of adsorbent used 4 gram resulted in average absorption of 81.14 percent and 94.15 percent, respectively, while variations in the adsorbent activation method with the activation process and variations in the adsorbent activation method without the activation process resulted in an average absorption of 81.14 % and 94.15 %. respectively, while the average value of the adsorption capacity in The adsorption model isotherm langmuir with R2 value of 0,6537 is suitable for the adsorption process employing teakwood sawdust adsorbent.